2011
DOI: 10.1016/j.metabol.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Total and high–molecular weight adiponectin in women with the polycystic ovary syndrome

Abstract: Objective-Adiponectin, an adipokine with antidiabetic properties, forms multimers, and the high molecular weight (HMW) form most closely correlates with insulin sensitivity. Therefore, we hypothesize that HMW adiponectin levels are decreased in women with polycystic ovary syndrome (PCOS), a condition characterized by insulin resistance, compared to normal controls, and that HMW adiponectin correlates with testosterone and insulin sensitivity.Design and patients-Cross-sectional study involving 13 women with PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
3
16
2
1
Order By: Relevance
“…Previous studies have reported conflicting results; some groups documented a decrease in adiponectin levels in women with PCOS compared with those in BMI-matched controls, whereas other studies found no differences in adiponectin levels between these groups [23]. Adiponectin levels tended to be lower in women with PCOS than in the controls in our study, but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 89%
“…Previous studies have reported conflicting results; some groups documented a decrease in adiponectin levels in women with PCOS compared with those in BMI-matched controls, whereas other studies found no differences in adiponectin levels between these groups [23]. Adiponectin levels tended to be lower in women with PCOS than in the controls in our study, but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 89%
“…It must be emphasized that the change in adipocyte size observed here was small and did not result in associated changes in adipocyte insulin sensitivity (Lundgren et al, 2007) or changes in circulating levels of the majority of adipokines measured (Scherer and Trujillo, 2006; Skurk et al, 2007). In PNA mice, there was a strong trend for decreased adiponectin in the fed state, which is in agreement with reduced adiponectin levels in women with PCOS (Wickham et al, 2010). Further, leptin levels were not reduced by fasting in PNA mice, suggesting altered regulation of this hormone, which is permissive for fertility (Moschos et al, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Adiponectin displays cardio-protective and anti-inflammatory properties [42, 43]. Previous reports on serum adiponectin levels in women with PCOS have been conflicting, with some showing lower levels and others showing no differences [44-46]. Our study showed a three-fold reduction in total adiponectin levels compared to controls but with no difference in the gene expression of adiponectin in the adipose tissue.…”
Section: Discussionmentioning
confidence: 39%